ScRNA-seq and spatial transcriptomics: exploring the occurrence and treatment of coronary-related diseases starting from development - Liu, Can; Yang, Fan; Su, Xin; Zhang, Zhenpeng; Xing, Yanwei (Frontiers in Cardiovascular Medicine, 2023)
Single-cell RNA sequencing (scRNA-seq) is a new technology that can be used to explore molecular changes in complex cell clusters at the single-cell level. Single-cell spatial transcriptomic technology complements the cell-space location information lost during single-cell sequencing. Coronary artery disease is an important cardiovascular disease with high mortality rates. Many studies have explored the physiological development and pathological changes in coronary arteries from the perspective of single cells using single-cell spatial transcriptomic technology. This article reviews the molecular mechanisms underlying coronary artery development and diseases as revealed by scRNA-seq combined with spatial transcriptomic technology. Based on these mechanisms, we discuss the possible new treatments for coronary diseases.